Application of Peer Tutor as A Solution to Overcome Aggression Behavior of Elementary School Students - Machmudah,; Kelly, Estalita; Yuniwati, Esy Suraeni; Rahman, Syahnur; Nurjanah, Siti; Eva, Nur; Rahmawati, Hetti (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine: the type of aggression behavior, the application of peer tutoring methods in overcoming the aggression behavior of third-grade students of elementary schools, and their obstacles and solutions. This research uses descriptive qualitative research methods. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation/display data, and drawing conclusions. Data validity checking techniques using triangulation techniques and sources. The results showed that the type of aggression behavior that occurred in class III SDI Nurul Huda was physical aggression and verbal aggression. Then the end of the application of this peer tutor method showed positive interactions between victims and perpetrators, although verbal aggression still suffered a lot of declines, this was because the perpetrator is accustomed to talking harshly. So that it can be said this application is quite successful with a note followed by other forms of therapy or interventions to overcome the behavior of verbal aggression.